1995
DOI: 10.1097/00005392-199502000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Function of En Bloc Infant Kidney Transplants: A Preliminary Study

Abstract: We evaluated the growth and function of 21 pairs of en bloc infant kidneys transplanted into adult recipients. Serum creatinine, 99mtechnetium-diethylenetriaminepentaacetic acid glomerular filtration rates, kidney volumes and resistive indexes were determined at 1 to 3, 3 to 6 and beyond 6 months, and compared using repeated measures analysis of variance tests. En bloc kidneys grew at a statistically significant rate (p < 0.001), for example nearly 2-fold in 3 to 6 months (209 +/- 69 cc from 132 +/- 70 cc), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 9 publications
7
29
0
1
Order By: Relevance
“…Based on animal studies and experience from clinical settings, en bloc grafts increase in size rapidly to adapt to the host environment [4,[10][11][12][13]. This was supported by our study, in which eGFR was significantly higher as far out as 5 years after transplantation, for recipients of en bloc kidneys compared with recipients of standard deceased donor kidneys.…”
Section: Other Benefits Of En Bloc Transplantssupporting
confidence: 74%
“…Based on animal studies and experience from clinical settings, en bloc grafts increase in size rapidly to adapt to the host environment [4,[10][11][12][13]. This was supported by our study, in which eGFR was significantly higher as far out as 5 years after transplantation, for recipients of en bloc kidneys compared with recipients of standard deceased donor kidneys.…”
Section: Other Benefits Of En Bloc Transplantssupporting
confidence: 74%
“…Most of the recent expansion in organ donation has occurred at the older extreme of age [1] . However, unlike kidneys from older donors, kidneys transplanted from pediatric donors into adult recipients have the capacity to grow to a normal adult renal size within a few months of KT and represent an underutilized resource [39] . Both conversion and utilization rates are lower with younger DD age [3,31,33] .…”
Section: Discussionmentioning
confidence: 99%
“…In their series of 22 en bloc kidney transplants, Satterthwaite et al 1 reported one venous thrombosis (4.5%) and two arterial thrombosis (9%), and all three grafts were lost. In their series of 45 patients, Nghiem et al 7 had six cases of venous thrombosis (13%), and all were lost. Merkel et al 4 had 25% of renal artery stenosis as a result of acute rejection, and all were corrected by microangioplasty.…”
Section: Discussionmentioning
confidence: 98%
“…Nghiem et al showed that when en bloc kidneys were used, they grew nearly two-fold in 3-6 months, and approached three-fold at six months, and similarly, glomenular filtration rates increased almost fourfold and five-fold during the same periods. 7 In another series by Nghiem 8 in which 20 en blocs were performed, the donors weighed less than 15 kg. One graft (5%) was lost due to venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%